Tinjauan Yuridis Terhadap Anak Berkewarga-negaraan Ganda Dalam Prespektif Hukum Nasional Dan Hukum Internasional - Fattah, Ilhamda; Deliana, Evi; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Law Number 12 Year 2006 Concerning Citizenship is the legal basis for the protection of children withdual nationality. Children with dual nationality are subject to two jurisdictions, and when examined in terms ofinternational law dual citizenship has potential problems, for example in terms of determining personal statusbased on the principle of nationality. Therefore, the purpose of this thesis writing is: First, the knowledge ofjuridical review of children with dual nationality in the perspective of national law. Secondly, the knowledge ofjuridical review of children with dual nationality in the practice of other countries.Type of research is the type of normative research is a study that discusses the comparison of laws insome countries. Sources of data used are primary data, secondary data and tertiary data. data collectiontechniques in this study by using literature review method that researchers analyze based on books, legislationand other literature related to the problems studied.The conclusions can be obtained from the research results are: First, in the perspective of national lawthat is based on Article 6 of Law Number 12 Year 2006 About Citizenship is granted the freedom for dualcitizenship until the children are 18 years old or until they get married. After the age of 18 years or married thechildren must choose their citizenship, whether to follow their father or become citizen. Secondly, the practiceof other countries such as according to Chinese law every citizen of the treaty countries (Indonesia-RRT) willbe given two years to choose one of citizenship. According to German law the children of foreigners born inGermany automatically become German citizens, provided that both parents of the child live in Germanylegally and within the specified period of the German citizenship law. Suggestion writer that is need to do effortprotection of childhood dual citizen and to realize welfare of child by giving guarantee to fulfill its rights andexistence of treatment without discrimination.Keywords: Children Dual Citizenship -Prespectives of National Law- International Law Perspective